2011
DOI: 10.3171/2011.7.focus1134
|View full text |Cite
|
Sign up to set email alerts
|

Complications related to instrumentation in spine surgery: a prospective analysis

Abstract: Object Prospective examination of perioperative complications in spine surgery is limited in the literature. The authors prospectively collected data on patients who underwent spinal fusion at a tertiary care center and evaluated the effect of spinal fusion and comorbidities on perioperative complications. Methods Between May and December 2008 data were collected prospectively in 248 patients admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 31 publications
0
33
2
Order By: Relevance
“…Instrumentation failure occurred in 8.2% of cases and pseudoarthrosis (assessed independently by a radiologist) in 2.4%. Instrumentation failure rates in the present study, however, were found to be greater in the setting of an infection compared with noninfection settings, in which rates approximate 2% (6). Pseudoarthrosis, in contrast, was only 2.4% compared with reported rates of 17%e24% in the literature (19,20), a phenomenon that has been attributed to "spontaneous" fusion in the setting of a spinal infection (3).…”
Section: Key Resultscontrasting
confidence: 51%
“…Instrumentation failure occurred in 8.2% of cases and pseudoarthrosis (assessed independently by a radiologist) in 2.4%. Instrumentation failure rates in the present study, however, were found to be greater in the setting of an infection compared with noninfection settings, in which rates approximate 2% (6). Pseudoarthrosis, in contrast, was only 2.4% compared with reported rates of 17%e24% in the literature (19,20), a phenomenon that has been attributed to "spontaneous" fusion in the setting of a spinal infection (3).…”
Section: Key Resultscontrasting
confidence: 51%
“…A large proportion of patients underwent instrumentation procedures, which have been associated with an increased incidence of complications as well. 5 A limitation of the current study is that complications such as deep wound infections may surface or lead to readmission beyond 30 postoperative days. This might lead to an underestimate of their true impact on health expenditures using the current methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The usual limitations to analysis apply, such as the low complication rate due to recall bias. 3 Still, in just 4 years, intrawound vancomycin use has been reported with an extremely low rate of adverse events in 6701 patients. This is even more impressive considering that all of these postoperative seromas were treated with wound revisions without any further events, and all manifestations of systemic toxicity such as nephropathy and ototoxicity were rare and transient.…”
Section: Discussionmentioning
confidence: 99%